An Atypical Case of Apical Hypertrophic Cardiomyopathy: Absence of Giant T Waves in spite of Extreme Apical Wall Hypertrophy - Elias Sanidas; Maria Bonou; Georgios Anastasiadis; Georgios Tzanis; John Barbetseas (Case Reports in Cardiology)
Apical hypertrophic cardiomyopathy is an uncommon variant of hypertrophic cardiomyopathy, with hypertrophy mainly affecting the apex of the left ventricle. We hereby describe a case of an octogenarian female patient who was randomly diagnosed with AHCM due to other comorbidities.